2002
DOI: 10.1007/s00122-002-1167-y
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus lines with rearranged Arabidopsis mitochondria display CMS and a range of developmental aberrations

Abstract: Numerous Brassica napus (+) Arabidopsis thaliana somatic hybrids were screened for male sterility and aberrant flower phenotypes. Nine hybrids were selected and backcrossed recurrently to B. napus. The resulting lines displayed stable maternal inheritance of flower phenotypes. Nuclear and organellar genomes were characterized molecularly using RFLP analysis. No DNA from A. thaliana was found in the nuclear genome after six back-crosses, whilst the mitochondrial genomes contained rearranged DNA from both A. tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 36 publications
8
62
0
Order By: Relevance
“…Similar types of variations were also observed in some Brassica alloplasmic cytoplasm, e.g., the Raphnnus/Ogura (Bannerot et al 1974), species cross B. nigra (L) Koch/B. oleracea L. (Pearson 1972) and B. napus with Arabidopsis cytoplasm (Leino et al 2003). In higher plants, flower development mechanism has been interpreted through the functioning of ABC model, where mutation and over-expression of these genes might lead to homeotic transformations in the flower organization (Zubko 2004).…”
Section: Discussionsupporting
confidence: 53%
“…Similar types of variations were also observed in some Brassica alloplasmic cytoplasm, e.g., the Raphnnus/Ogura (Bannerot et al 1974), species cross B. nigra (L) Koch/B. oleracea L. (Pearson 1972) and B. napus with Arabidopsis cytoplasm (Leino et al 2003). In higher plants, flower development mechanism has been interpreted through the functioning of ABC model, where mutation and over-expression of these genes might lead to homeotic transformations in the flower organization (Zubko 2004).…”
Section: Discussionsupporting
confidence: 53%
“…The radish Ogura CMS cytoplasm in the B. napus background results in altered floral morphology (Figure 2). Individual cybrid lines containing the B. napus nuclear genome and recombinant mtDNA derived from a combination of B. napus and Arabidopsis exhibited homeotic transformation of anthers to carpels and some disturbances in vegetative growth (Leino et al, 2003). In carrot, lines containing a CMS cytoplasm may exhibit either a petaloid (Figure 2) or a carpeloid phenotype, depending on nuclear background.…”
Section: Effects Of Cms-encoding Genes On Floral Morphologymentioning
confidence: 99%
“…Hanna for eight generations resulting in lines with the nuclear genome of B. napus. Southern analysis (Leino et al, 2003) and RFLP analysis (data not shown) demonstrated that the chloroplast genome was of B. napus while the mitochondrial genome had rearranged DNA inherited from B. napus and A. thaliana. Both lines are male sterile and display vegetative aberrations that are stable through successive generations.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In the present work, two alloplasmic CMS lines of Brassica napus containing rearranged Arabidopsis thaliana mtDNA (Forsberg et al, 1998;Leino et al, 2003) have been investigated and compared to the parental fertile B. napus cultivar. Alloplasmic lines frequently display homeotic conversions that have been attributed to the disturbed interactions between nuclei and mitochondria.…”
Section: Introductionmentioning
confidence: 99%